Corruption and innovation: a grease or sand relationship? - Prashanth Mahagaonkar (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
This paper provides a firm-level empirical analysis on the ways in which corruption affects innovative activity. Particularly with respect to the African continent that is striving to reconcile with instability and poverty, this issue seems to be of utmost importance. Using a newly available dataset on African firms, it is shown that corruption has a negative effect on product innovation and organisational innovation. Corruption does not affect process innovation while it facilitates marketing innovation.
Keywords: D73; O14; O31; H11; H25; 330; Corruption; Developing Economies; Product Innovation; Process Innovation; Organisational Innovation; marketing Innovation; Taxation; Korruption; Innovation; Organisatorischer Wandel; Afrika